2016
DOI: 10.3233/blc-150027
|View full text |Cite
|
Sign up to set email alerts
|

Independent Replication of Published Germline Polymorphisms Associated with Urinary Bladder Cancer Prognosis and Treatment Response

Abstract: Background:Many studies investigated the prognostic or predictive relevance of single nucleotide polymorphisms (SNPs) in biologically plausible genes in urinary bladder cancer (UBC) patients. Most published SNP associations have never been replicated in independent patient series.Objective:To independently replicate all previously reported associations between germline SNPs and disease prognosis or treatment response in UBC.Methods:A Pubmed search was performed to identify studies published by July 1, 2014 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
(31 reference statements)
0
20
0
3
Order By: Relevance
“…The development of breast cancer is very complicated, and includes environmental and genetic elements. As one of the genetic variants, single nucleotide polymorphisms (SNPs) are widely used to predict the disease risk, prognosis, and 2 Arch Med Sci clinical outcome [2,3]. Accumulative investigations have found that SNPs in tumor oncogenes or suppressor genes could play a vital role in breast cancer genetic susceptibility [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The development of breast cancer is very complicated, and includes environmental and genetic elements. As one of the genetic variants, single nucleotide polymorphisms (SNPs) are widely used to predict the disease risk, prognosis, and 2 Arch Med Sci clinical outcome [2,3]. Accumulative investigations have found that SNPs in tumor oncogenes or suppressor genes could play a vital role in breast cancer genetic susceptibility [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As an oncogene, HOTAIR lncRNA is involved in the initiation and progression of cancer and also plays a key role in promoting malignancy, suggesting it might be a novel prognostic biomarker and a potential target in cancer therapy . As a type of genetic variant, SNP is widely used in the prediction of disease risk, clinical outcome, and prognosis . It is interesting to note that multiple SNPs across the entire HOTAIR gene have been demonstrated to influence the cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…29,30 As a type of genetic variant, SNP is widely used in the prediction of disease risk, 31 clinical outcome, 32 and prognosis. 33 It is interesting to note that multiple SNPs across the entire HOTAIR gene have been demonstrated to influence the cancer risk. [34][35][36][37] To our knowledge to date, the association between HOTAIR gene polymorphisms and neuroblastoma susceptibility has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Генотип TT -чувствительность к БЦЖ TT genotype -sensitivity to BCG [34] обнаружена ассоциация генотипа СС полиморфизма 844T / C в промоторе FASL с гиперэкспрессией этого гена и уменьшением безрецидивного периода после ТУР и БЦЖ-терапии [31]. В различных популяциях показана ассоциация генотипа GG полиморфизма rs187 238 в гене IL18 с эффективностью БЦЖ-терапии [30]. По данным метаанализа, включающего 113 оригинальных работ, показана ассоциация с эффективностью БЦЖ-терапии гомозиготных генотипов полиморфизмов в генах IL6, IL8, IL2RA, IL17RA, TRAILR1, TNFA, NFKB, IFNG, TGFB (см.…”
unclassified
“…Обзоры БЦЖ-терапии [32]. В метаанализе с рецидивом после БЦЖ-терапии также был ассоциирован генотип ТТ полиморфизма rs1 799 793 в гене ERCC2, участвующего в эксцизионной репарации [30]. Результаты исследования эпигенетического репрограммирования моноцитов в ответ на инстилляцию вакцины БЦЖ показали, что с рецидивом ассоциирован аллель С полиморфизма rs3 759 601 в гене ATG2B, участвующего в аутофагии [28].…”
unclassified